Exploring Parents’ Perceptions of Early Literacy Development in Early Childhood Education - Popi Rosepti; Catur Niasari; Rosmita Chaerunnisa (Universitas Negeri Makassar, 2024)
This study explores early literacy concepts for young children among parents in low-class communities. It focuses on parents’ interpretations of their children’s development in early literacy and how these influence due to their children’s education. The aim of the research is to illuminate parents’ interpretations regarding early literacy in their children’s education. Through the classical phenomenological approach, seven mothers were interviewed, and the collected data was analyzed using Colaizzi’s method to describe the themes. The findings reveal that they perceived early literacy as an ability to read and write that children must achieve before they are seven years old. They also mentioned it for fulfilling entry requirements for the primary level, avoiding negative stigma from other parents, labeling smart children, and parents’ anxiety for children’s confidence in the future. As a consequence, it allows parents to have reading class preparation, over-involvement in children’s learning activities, providing learning posters, and parents’ home teaching. This study also discussed the concept of early literacy based on human development theories and how it can contribute to sustaining and empowering parents dealing with meaningful learning in cultivating literacy for children in the perception year.